Impact of private tutoring for university admission and subsequently on students' academic results - Alam, Gazi Mahabubul; Forhad, Md Abdur Rahman (Emerald Publishing, 2023)
Purpose: Education can be classified into formal and informal sectors—the first category as a regular schooling system and the latter category as private tutoring. After completing secondary education, students in many countries receive education from private tutoring to get admission into the university. This study examines the effect of private tutoring on university admission and subsequent students' academic achievement at the university level. Design/methodology/approach: Using survey data from Bangladesh as a case study, this study employs a two-stage least squares (2SLS) methodology. Findings: Considering that coaching centers offer services such as private tutoring, this study finds that an informal education for admission greatly helps academic achievement. Students who benefit from informal schooling are more likely to achieve higher grades in subsequent programs. Originality/value: This study strongly suggests that formal education at the secondary school level is unable to meet the academic expectations that are demanded at the tertiary level. This forces the development of private tutoring, which supports the students from more financially well-off families to perform well at the cost of educational disparity.